Timing and delivery route effects of cecal microbiome transplants on Salmonella Typhimurium infections in chickens: potential for in-hatchery delivery of microbial interventions - Sian Pottenger; Amyleigh Watts; Amy Wedley; Sue Jopson; Alistair C. Darby; Paul Wigley (Animal Microbiome, 2023)
Abstract Background Exposure to microbes early in life has long-lasting effects on microbial community structure and function of the microbiome. However, in commercial poultry settings chicks are reared as a single-age cohort with no exposure to adult birds which can have profound effects on microbiota development and subsequent pathogen challenge. Microbiota manipulation is a proven and promising strategy to help reduce pathogen load and transmission within broiler flocks. However, administration of microbiota transplant products in a hatchery setting may prove challenging. Effective administration strategies are dependent on key factors, such as; the age of chicks receiving interventions and mode of delivery. This study aimed to assess these two aspects to provide supporting evidence towards microbiome manipulation strategies for use in commercial hatcheries. Results Manipulation of the microbiota between 4 and 72 h of hatch markedly reduced faecal shedding and colonisation with the foodborne pathogen Salmonella enterica serovar Typhimurium (ST4/74). Administration of transplant material via spray or gel drop delivery systems had minimal effect on the protection conferred with fewer birds in transplant groups shown to shed ST4/74 in the faeces compared to PBS-gavaged control birds. Analysis of the microbiome following transplantation demonstrated that all transplant groups had higher diversity and species richness than non-transplant groups during the first week of life and the early stages of infection with ST47/4.The relative abundance of the bacterium Faecalibacterium prausnitzii was significantly higher in CMT groups compared to PBS controls. The presence of F. prausnitzii was also shown to increase in PBS-challenged birds compared to unchallenged birds potentially indicating a role of this bacterium in limiting Salmonella infections. Conclusions This study demonstrated that administration of microbiome transplants, using methods that would align with hatchery practices, effectively reduced colonisation and shedding of Salmonella in chickens. Age of chicks at microbiome administration had limited effect on the diversity and composition of the microbiome and conferred protection against Salmonella infections. Traditional hatchery delivery systems, such as spray or gel-drop, are sufficient to transfer donor material, alter the microbiome and confer protection against Salmonella. This study helps highlight the opportunity for use of microbiome modification methods within the hatchery.